Preparation method of micron dendritic copper powder

By using copper acetate and polysaccharide in liquid phase reduction method for hydrothermal reaction, micron-sized branched copper powder was prepared, solving the problems of complex process and high cost in the prior art, and achieving high efficiency and low cost copper powder preparation and show superiority in multiple application areas.

CN119187546APending Publication Date: 2024-12-27NORTHWEST INSTITUTE FOR NONFERROUS METAL RESEARCH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411607827.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The prior art has problems such as complex process, low production efficiency, high cost, difficult waste liquid treatment and easy agglomeration of products when preparing branched copper powder. In particular, it is difficult to achieve efficient and controllable preparation under mild conditions.

Method used

Using copper acetate as raw material, using polysaccharides such as glucose, fructose, sucrose or maltose as green reducing agents, micron branched copper powder is prepared under mild conditions through hydrothermal reactions, simplifying the process flow, avoiding violent reactions, and achieving low cost and high efficiency. Controllable preparation.

Benefits of technology

It realizes the preparation of branched copper powder in micron size, simplifies the process flow, reduces energy consumption, avoids agglomeration, is suitable for industrial production, and is widely used in the fields of antibacterial and conductive fillers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119187546A_ABST
    Figure CN119187546A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of micron dendritic copper powder. The method comprises the following steps: 1, adding a reducing agent and polyvinylpyrrolidone into deionized water, and uniformly stirring to obtain a clear solution; 2, adding copper acetate or a copper acetate solution into the clear solution, and uniformly stirring to obtain a mixed solution; 3, performing hydrothermal reaction on the mixed solution to obtain a reaction product; and 4, settling and washing the reaction product, and performing vacuum drying to obtain the micron dendritic copper powder. The micron dendritic copper powder is prepared by taking copper acetate as a raw material, using a green reducing agent and adopting a hydrothermal reaction, so that the problem that agglomeration is easy to occur when the dendritic copper powder is prepared by an electrolytic method is avoided, the technical limitation that acute reducing agents such as red phosphorus need to be used at present is effectively solved, and the method has the advantages of simplicity in operation, low cost, greenness, environmental friendliness and the like; the copper powder is suitable for the fields of antibiosis, printed circuit boards, conductive fillers, radio frequency electronic tags, catalysis, wave absorption, electromagnetic shielding and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal conductive materials, and in particular relates to a method for preparing micron dendritic copper powder. Background Art

[0002] With the development of nanomaterial technology and the iterative needs of electronic products, electronic conductive materials play an important role. The application of precious metal materials is partially limited due to their high prices and scarce resources. Ultrafine copper powder materials are widely used in conductive adhesives, conductive coatings, electrodes, and electromagnetic shielding due to their good conductivity.

[0003] Ultrafine copper powder can be divided into spherical, flaky and dendritic shapes according to its morphology. Dendritic copper powder has a large specific surface area and network structure, and has unique advantages for electron transport. At present, the most commonly used methods for preparing dendritic copper powder are electrolysis and chemical liquid phase reduction. Among them, the electrolytic method for preparing ultrafine copper powder has been the most studied technology. By changing parameters such as current density, reaction solution concentration, pH value, concentration and type of surfactant, dendritic copper powder of different sizes and morphologies can be obtained. Although this method can obtain ultrafine dendritic copper powder, due to the influence of concentration polarization and current efficiency during the electrolysis process, the prepared copper powder will generally have problems such as agglomeration and poor dispersibility. Moreover, the production efficiency of ultrafine copper powder prepared by electrolysis is relatively low, the power consumption is large, the waste liquid generated needs to be strictly treated before discharge, and the production cost is high.

[0004] The liquid phase reduction method uses redox technology to reduce divalent copper ions to copper element using a reducing agent. By adjusting different reaction parameters, a series of ultrafine copper powders with different morphologies and particle sizes are obtained. It has the advantages of simple process and low cost. The material morphology and size can be regulated in a simple liquid phase reaction. It is considered to be the most promising technology for industrial production. At present, some progress has been made in the preparation of dendritic copper powder by liquid phase reduction. The main method is to add a certain amount of red phosphorus to the precursor solution containing copper salt, and obtain dendritic copper powder through a violent hydrothermal reaction. Since the growth process of dendritic copper powder is relatively complicated, it is necessary to obtain the product of the desired morphology under special conditions. Therefore, designing a simple process scheme and developing a chemical liquid phase reduction method to prepare dendritic copper powder under mild conditions is still a challenging research task. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing micron dendritic copper powder in view of the deficiencies of the above-mentioned prior art. The method adopts a chemical liquid phase reduction method, uses copper acetate as a raw material, and uses polysaccharide as a green reducing agent to prepare micron dendritic copper powder, which solves the problems of the current liquid phase reduction method, such as the complex process and harsh reduction reaction conditions, and has a simple process and mild reducing agent performance, thereby realizing low-cost, efficient and controllable preparation of dendritic copper powder.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing micron dendrite copper powder, characterized in that the method comprises the following steps:

[0007] Step 1: adding a reducing agent and polyvinyl pyrrolidone into deionized water and stirring evenly to obtain a clear solution;

[0008] Step 2: adding copper acetate or copper acetate solution to the clear solution obtained in step 1 and stirring evenly to obtain a mixed solution;

[0009] Step 3: transferring the mixed solution obtained in step 2 to a hydrothermal reaction kettle, reacting at 100° C. to 120° C. for 10 h to 16 h to obtain a reaction product;

[0010] Step 4: The reaction product obtained in step 3 is sequentially washed with deionized water and anhydrous ethanol for sedimentation, and then placed in a vacuum drying oven for 4 hours to 8 hours to obtain micron dendritic copper powder.

[0011] The present invention first mixes a reducing agent, polyvinyl pyrrolidone and deionized water, then adds copper acetate or copper acetate solution, and obtains a micron dendritic copper powder material under hydrothermal reaction conditions. The present invention uses mild, green and environmentally friendly polysaccharides as a reducing agent, replaces the use of red phosphorus, a reducing agent in the existing preparation technology, effectively avoids the use of a violent reducing agent, and is conducive to the control of the reaction process and the regulation of the product morphology. At the same time, the overall technical solution design of the present invention is relatively simple, and there is no need to regulate the pH value of the solution. Only a small amount of surfactant needs to be added to achieve the assembly and growth of the micron dendritic copper powder. Since the size of the dendritic copper powder prepared by the present invention is relatively large, at the micron level, the product does not need to be centrifuged, and solid-liquid separation can be quickly achieved after standing. After multiple standing treatments, the product can be washed. The method is simple in process, low in energy consumption, and is conducive to industrial production.

[0012] The above-mentioned method for preparing micron dendritic copper powder is characterized in that the molar ratio of the reducing agent, polyvinyl pyrrolidone and deionized water in step 1 is 1: 0.17-0.89: 165-385. By controlling the molar ratio of the reducing agent and polyvinyl pyrrolidone, it is ensured that the product can nucleate, self-assemble and grow into a dendritic structure.

[0013] The above-mentioned method for preparing micron dendritic copper powder is characterized in that the reducing agent in step 1 is glucose, fructose, sucrose, maltose or galactose.

[0014] The above-mentioned method for preparing micron dendritic copper powder is characterized in that the molar ratio of copper acetate to reducing agent in the mixed solution in step 2 is 0.25 to 0.9: 1. By adjusting the molar ratio of copper acetate to reducing agent, it is ensured that divalent copper ions can be completely reduced by the reducing agent to obtain pure micron copper powder.

[0015] The above-mentioned method for preparing micron dendritic copper powder is characterized in that the molar ratio of copper acetate to water in the copper acetate solution in step 2 does not exceed 1: 275. By adjusting the molar ratio of copper acetate to solution water, the concentration of copper salt is effectively controlled to achieve the optimal solid-liquid ratio of the reaction.

[0016] The above-mentioned method for preparing a micron dendritic copper powder is characterized in that the sedimentation washing process described in step 4 is: adding the reaction product to deionized water, shaking it and then letting it stand, after the reaction product and the deionized water are separated, the supernatant is poured out, deionized water is added and this process is repeated 5 to 10 times, and then the reaction product is added to anhydrous ethanol, shaking it and then letting it stand, after the reaction product and the anhydrous ethanol are separated, the supernatant is poured out, anhydrous ethanol is added and this process is repeated 3 to 5 times.

[0017] The above-mentioned method for preparing micron dendritic copper powder is characterized in that the drying in step 4 is performed by using a vacuum drying oven, the vacuum drying temperature is 40° C. to 60° C., and the vacuum degree is -0.1 MPa.

[0018] Compared with the prior art, the present invention has the following advantages:

[0019] 1. The present invention adopts a chemical liquid phase reduction method, uses copper acetate as a raw material, uses polysaccharide as a green reducing agent, and prepares micron dendritic copper powder through a hydrothermal reaction, breaking the technical limitations of the electrolytic method for preparing dendritic copper powder, which is complex, polluting, and easy to agglomerate the product, and effectively solves the technical limitations of the current need to use violent reducing agents such as red phosphorus, and has the advantages of simple operation, low cost, and green environmental protection.

[0020] 2. The present invention uses glucose, fructose, sucrose, maltose or galactose as a reducing agent instead of the commonly used red phosphorus as a reducing agent, which can effectively avoid the occurrence of violent reactions in the system, is conducive to controlling the nucleation and growth process of the reaction, and regulating the morphology and size of the product copper powder.

[0021] 3. The equipment used in the present invention is simple, low-cost, and the process parameters are controllable, with high repeatability, which is convenient for large-scale production. The prepared micron dendritic copper powder has a wide range of applications in the fields of antibacterial, printed circuit boards, conductive fillers, wireless radio frequency electronic tags, catalysis, wave absorption, electromagnetic shielding, etc.

[0022] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a high-magnification SEM image of the micron dendritic copper powder prepared in Example 1 of the present invention.

[0024] Figure 2 This is a low-magnification SEM image of the micron dendritic copper powder prepared in Example 1 of the present invention.

[0025] Figure 3 This is the EDS energy spectrum of the micron dendritic copper powder prepared in Example 1 of the present invention.

[0026] Figure 4 This is a SEM image of the micron dendritic copper powder prepared in Example 2 of the present invention.

[0027] Figure 5 This is a SEM image of the micron dendritic copper powder prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0028] Example 1

[0029] This embodiment includes the following steps:

[0030] Step 1, adding glucose and polyvinyl pyrrolidone into deionized water and stirring evenly to obtain a clear solution; the molar ratio of glucose, polyvinyl pyrrolidone and deionized water is 1:0.3:270, and the molar amount of glucose is 0.01 mol;

[0031] Step 2: Add the copper acetate solution to the clear solution obtained in step 1 and stir evenly to obtain a mixed solution; the molar ratio of copper acetate to glucose in the mixed solution is 0.8:1, the molar amount of copper acetate in the copper acetate solution is 0.008 mol, and the molar ratio of copper acetate to water in the copper acetate solution is 1:70;

[0032] Step 3: Transfer the mixed solution obtained in step 2 to a hydrothermal reactor and react in an oven at 120° C. for 12 hours to obtain a reaction product;

[0033] Step 4, the reaction product obtained in step 3 is sequentially washed with deionized water and anhydrous ethanol by sedimentation, and then placed in a vacuum drying oven and vacuum dried for 8 hours at 40°C and a vacuum degree of -0.1MPa to obtain micron dendritic copper powder; the sedimentation washing process is as follows: the reaction product is added to deionized water, shaken and allowed to stand, after the reaction product and the deionized water are separated, the upper clear liquid is poured out, deionized water is added and this process is repeated 5 times, and then the reaction product is added to anhydrous ethanol, shaken and allowed to stand, after the reaction product and the anhydrous ethanol are separated, the upper clear liquid is poured out, anhydrous ethanol is added and this process is repeated 3 times.

[0034] Figure 1 This is a high-magnification SEM image of the micron dendrite copper powder prepared in this example. Figure 1 It can be seen that the copper powder has a branch-like structure with a diameter distribution of 30μm to 50μm. It is assembled into a branch-like structure by multiple micro-nano needle-rod structures. No other morphology or other impurity products appear, indicating that the copper powder has a high purity.

[0035] Figure 2 This is a low-magnification SEM image of the micron dendrite copper powder prepared in this example. Figure 2 It can be seen that the copper powder has good morphological uniformity and is highly dispersed without agglomeration.

[0036] Figure 3 This is the EDS spectrum of the micron dendrite copper powder prepared in this example. Figure 3 It can be seen that the product copper powder is mainly composed of Cu element and contains only very small amounts of C and O elements (affected by the conductive tape), indicating that the product is indeed single element Cu, and further proves that the purity of the obtained product copper powder is high.

[0037] The reducing agent in step 1 of this embodiment can also be replaced by sucrose, maltose or galactose.

[0038] Example 2

[0039] This embodiment includes the following steps:

[0040] Step 1, adding glucose and polyvinyl pyrrolidone into deionized water and stirring evenly to obtain a clear solution; the molar ratio of glucose, polyvinyl pyrrolidone and deionized water is 1:0.45:350, and the molar amount of glucose is 0.02 mol;

[0041] Step 2: Add the copper acetate solution to the clear solution obtained in step 1 and stir evenly to obtain a mixed solution; the molar ratio of copper acetate to glucose in the mixed solution is 0.5:1, the molar amount of copper acetate in the copper acetate solution is 0.01 mol, and the molar ratio of copper acetate to water in the copper acetate solution is 1:275;

[0042] Step 3: Transfer the mixed solution obtained in step 2 to a hydrothermal reactor and react in an oven at 100° C. for 16 hours to obtain a reaction product;

[0043] Step 4, the reaction product obtained in step 3 is sequentially washed with deionized water and anhydrous ethanol by sedimentation, and then placed in a vacuum drying oven and vacuum dried for 4 hours at 60°C and a vacuum degree of -0.1MPa to obtain micron dendritic copper powder; the sedimentation washing process is as follows: the reaction product is added to deionized water, shaken and allowed to stand, after the reaction product and the deionized water are separated, the upper clear liquid is poured out, deionized water is added and this process is repeated 10 times, and then the reaction product is added to anhydrous ethanol, shaken and allowed to stand, after the reaction product and the anhydrous ethanol are separated, the upper clear liquid is poured out, anhydrous ethanol is added and this process is repeated 3 times.

[0044] Figure 4 This is the SEM image of the micron dendrite copper powder prepared in this example. Figure 4 It can be seen that the copper powder of the product is a micron-dendritic structure, and no other morphologies or other impurity products appear in the copper powder, indicating that the obtained copper powder has a high purity, is highly dispersed, and has no agglomeration phenomenon.

[0045] Example 3

[0046] This embodiment includes the following steps:

[0047] Step 1, adding fructose and polyvinyl pyrrolidone into deionized water and stirring evenly to obtain a clear solution; the molar ratio of fructose, polyvinyl pyrrolidone and deionized water is 1:0.89:700, and the molar amount of fructose is 0.01 mol;

[0048] Step 2: adding the clear solution obtained in step 1 to the copper acetate solution and stirring evenly to obtain a mixed solution; the molar ratio of copper acetate to fructose in the mixed solution is 0.7:1, the molar amount of copper acetate in the copper acetate solution is 0.015 mol, and the molar ratio of copper acetate to water in the copper acetate solution is 1:150;

[0049] Step 3: Transfer the mixed solution obtained in step 2 to a hydrothermal reactor and react in an oven at 110° C. for 12 h to obtain a reaction product;

[0050] Step 4, the reaction product obtained in step 3 is sequentially washed with deionized water and anhydrous ethanol by sedimentation, and then placed in a vacuum drying oven and vacuum dried for 6 hours at 50°C and a vacuum degree of -0.1MPa to obtain micron dendritic copper powder; the sedimentation washing process is as follows: the reaction product is added to deionized water, shaken and allowed to stand, after the reaction product and the deionized water are separated, the upper clear liquid is poured out, deionized water is added and this process is repeated 8 times, and then the reaction product is added to anhydrous ethanol, shaken and allowed to stand, after the reaction product and the anhydrous ethanol are separated, the upper clear liquid is poured out, anhydrous ethanol is added and this process is repeated 5 times.

[0051] Figure 5 This is the SEM image of the micron dendrite copper powder prepared in this example. Figure 4 It can be seen that the copper powder of the product is a micron-dendritic structure, and no other morphologies or other impurity products appear in the copper powder, indicating that the obtained copper powder has a high purity, is highly dispersed, and has no agglomeration phenomenon.

[0052] Example 4

[0053] This embodiment includes the following steps:

[0054] Step 1, adding glucose and polyvinyl pyrrolidone into deionized water and stirring evenly to obtain a clear solution; the molar ratio of glucose, polyvinyl pyrrolidone and deionized water is 1:0.17:165, and the molar amount of glucose is 0.01 mol;

[0055] Step 2: adding copper acetate to the clear solution obtained in step 1 and stirring evenly to obtain a mixed solution; the molar ratio of copper acetate to glucose in the mixed solution is 0.25:1, and the molar amount of copper acetate is 0.0025 mol;

[0056] Step 3: Transfer the mixed solution obtained in step 2 to a hydrothermal reactor and react in an oven at 120° C. for 12 hours to obtain a reaction product;

[0057] Step 4, the reaction product obtained in step 3 is sequentially washed with deionized water and anhydrous ethanol by sedimentation, and then placed in a vacuum drying oven and vacuum dried for 8 hours at 40°C and a vacuum degree of -0.1MPa to obtain micron dendritic copper powder; the sedimentation washing process is as follows: the reaction product is added to deionized water, shaken and allowed to stand, after the reaction product and the deionized water are separated, the upper clear liquid is poured out, deionized water is added and this process is repeated 5 times, and then the reaction product is added to anhydrous ethanol, shaken and allowed to stand, after the reaction product and the anhydrous ethanol are separated, the upper clear liquid is poured out, anhydrous ethanol is added and this process is repeated 3 times.

[0058] After testing, the product of this embodiment is red copper powder.

[0059] Example 5

[0060] This embodiment includes the following steps:

[0061] Step 1, adding glucose and polyvinyl pyrrolidone into deionized water and stirring evenly to obtain a clear solution; the molar ratio of glucose, polyvinyl pyrrolidone and deionized water is 1:0.3:385, and the molar amount of glucose is 0.01 mol;

[0062] Step 2: Add the copper acetate solution to the clear solution obtained in step 1 and stir evenly to obtain a mixed solution; the molar ratio of copper acetate to glucose in the mixed solution is 0.9:1, the molar amount of copper acetate in the copper acetate solution is 0.008 mol, and the molar ratio of copper acetate to water in the copper acetate solution is 1:70;

[0063] Step 3: Transfer the mixed solution obtained in step 2 to a hydrothermal reactor and react in an oven at 120° C. for 12 hours to obtain a reaction product;

[0064] Step 4, the reaction product obtained in step 3 is sequentially washed with deionized water and anhydrous ethanol by sedimentation, and then placed in a vacuum drying oven and vacuum dried for 8 hours at 40°C and a vacuum degree of -0.1MPa to obtain micron dendritic copper powder; the sedimentation washing process is as follows: the reaction product is added to deionized water, shaken and allowed to stand, after the reaction product and the deionized water are separated, the upper clear liquid is poured out, deionized water is added and this process is repeated 5 times, and then the reaction product is added to anhydrous ethanol, shaken and allowed to stand, after the reaction product and the anhydrous ethanol are separated, the upper clear liquid is poured out, anhydrous ethanol is added and this process is repeated 3 times.

[0065] After testing, the product of this embodiment is red copper powder.

[0066] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing micron dendritic copper powder, characterized in that: The method comprises the following steps: Step 1: adding a reducing agent and polyvinyl pyrrolidone into deionized water and stirring evenly to obtain a clear solution; Step 2: adding copper acetate or copper acetate solution to the clear solution obtained in step 1 and stirring evenly to obtain a mixed solution; Step 3: transferring the mixed solution obtained in step 2 to a hydrothermal reaction kettle, reacting at 100° C. to 120° C. for 10 h to 16 h to obtain a reaction product; Step 4: The reaction product obtained in step 3 is sequentially washed with deionized water and anhydrous ethanol for sedimentation, and then placed in a vacuum drying oven for 4 hours to 8 hours to obtain micron dendritic copper powder.

2. The method for preparing micron dendritic copper powder according to claim 1, characterized in that: The molar ratio of the reducing agent, polyvinyl pyrrolidone and deionized water in step 1 is 1:0.17-0.89:165-385.

3. The method for preparing micron dendritic copper powder according to claim 1, characterized in that: The reducing agent in step 1 is glucose, fructose, sucrose, maltose or galactose.

4. The method for preparing micron dendritic copper powder according to claim 1, characterized in that: The molar ratio of copper acetate to reducing agent in the mixed solution in step 2 is 0.25-0.9:

1.

5. The method for preparing micron dendritic copper powder according to claim 1, characterized in that: The molar ratio of copper acetate to water in the copper acetate solution in step 2 is no more than 1:

275.

6. The method for preparing micron dendritic copper powder according to claim 1, characterized in that: The sedimentation washing process described in step 4 is: adding the reaction product to deionized water, shaking it and letting it stand, after the reaction product and the deionized water are separated by layers, pouring out the supernatant, adding deionized water and repeating this process 5 to 10 times, then adding the reaction product to anhydrous ethanol, shaking it and letting it stand, after the reaction product and the anhydrous ethanol are separated by layers, pouring out the supernatant, adding anhydrous ethanol and repeating this process 3 to 5 times.

7. The method for preparing micron dendritic copper powder according to claim 1, characterized in that: The drying in step 4 is performed by using a vacuum drying oven, the vacuum drying temperature is 40°C to 60°C, and the vacuum degree is -0.1MPa.